Penegakan Hukum Diwilayah Laut Maluku oleh Lantamal IX Ambon - Lucia Charlota Octovina Tahamata (Balobe Law Journal, 2021)
Introduction: Law enforcement in the sea area by Lantamal IX Ambon, is faced with, supporting factors and inhibiting factors. Purposes of the Research: This study aims to determine and analyze how Lantamal IX Ambon conducts law enforcement in the Maluku sea area.Methods of the Research: The research method used is a normative research method using a statute approach approach conceptual approach and analytical approach. Document study techniques and study analysis use qualitative analysis. Results of the Research: The results showed that in order to achieve efficiency and effectiveness in deploying the force of the Navy, it is faced with budget constraints, technical conditions of defense equipment and the expected level of capability and escalation of threats, it is necessary to reform policies regarding law enforcement facilities and infrastructure towards improvements in accordance with science. and modernization today due to the reality of the geographical configuration of the country's territory in the form of an archipelago with 2/3 of its territory being water, of course logically Indonesia needs a strong and reliable Navy. There is an overlap in legal and institutional arrangements at sea, so it is necessary to synergize with the institutional aspects of law enforcement officials who have the authority.